Blood Libel and the Pius War: A Bibliographic Review of the Roman Catholic Church and the Holocaust. (1st May 2020) - Johnson, Wendell G.
Abstract: The reaction of the Roman Catholic Church and its Pontiff to the Holocaust continues to elicit scholarly debate. The Church was strident in its denunciation and condemnation of Bolshevism and Communism. Did it remain culpably silent in its reactions to Nazism in Germany and Fascism in Italy, two political movements which led to the destruction of Europe's Jewish population? This study provides a review of the policies and actions of Pope Pius XI (Achille Ratti) and his successor Pope Pius XII (Eugenio Pacelli). In the view of Holocaust scholars (e.g. Goldhagen and Zuccotti) the role of Pius XII represents a blight on the reputation of the Roman Catholic Church. Also included are biographical sketches of two Catholic priests (Pere Marie-Benoit and Jozef Tiso) who met very different fates after the conclusion of the Second World War.